Rudy Kelly’s Eyes: Chris Hedges and Joe Sacco’s Days of Destruction, Days of Revolt - Øyvind Vågnes (European Journal of American Studies)
At first sight Chris Hedges and Joe Sacco’s Days of Destruction, Days of Revolt belongs solidly in the same tradition as books such as James Agee and Walker Evans’s classic Let Us Now Praise Famous Men (1941), which grew out of an assignment in 1936 to produce a magazine article on the conditions sharecropper families in the South lived under during the “Dust Bowl,” as well as William T. Vollmann’s 2007 book Poor People.Days of Destruction, Days of Revolt describes the predicament of the rapidly growing underclass in the States, victims of corporate capitalism in what Hedges refers to as “sacrifice zones,” areas that have been offered up for exploitation in the name of profit. The reader is introduced to despaired people living on the Pine Ridge Lakota reservation in South Dakota; the homeless of Camden, N.J.; migrant workers assigned to pick tomatoes in worker camps in Florida; and individuals suffering from and resisting mountain-top removal by coal companies in West Virginia. However, Days of Destruction, Days of Revolt departs from this tradition of social reportage in several significant ways, and my article will address how—with a particular focus on the book’s use of drawingsand comics reportage in the place of photography. What are the implications of this particular verbal-visual strategy? Interrogating the ethics of the drawn documentary image inevitably implies addressing its peculiar, somewhat paradoxical authenticity, and to think of how drawings differ from photographs in how they depict the world. In my discussion of this I’ll draw on both documentary and comics theory (Paul Ward, Hillary Chute, Charles Hatfield). I will argue that the use of drawn images in Days of Destruction, Days of Revolt results in a new form of what W.J.T. Mitchell calls “imagetext,” one that raises its fundamental social and political questions with energy, passion, and ethical integrity.